Social work students’ attitudes, self-efficacy, and concerns about clients with developmental and psychiatric disabilities in the UAE - Kuyini, Ahmed Bawa (2019)
This study examined the attitudes, self-efficacy beliefs, and con cerns of social work students in relation to working with clients with developmental disabilities and psychiatric (mental health) issues in the UAE. A four-part survey questionnaire—comprising Participants’ Background Information, Attitudes, Self-Efficacy, and Concerns about working withclients—was used to collect data. The data were analyzed using Descriptive statistics, t-tests, Regression, and ANOVA procedures. The results showed that participants’ atti tudes were less positive. They also reported low Self-efficacy beliefs and moderate-high concerns about working with these client groups. Some demographic variables (e.g. training) influenced atti tudes and Self-efficacy. Implications and recommendations relating to curriculum, teaching/course delivery and practice are discussed.